Performance evaluation of a photovoltaic park in Cyprus using irradiance sensors - Charalambides, Alexandros G.; Tapakis, Rogiros (My University, 2014)
The power output of Photovoltaic (PV) modules is directly affected by the presence of clouds, due to changes in the irradiance caused by the clouds, resulting in rapid fluctuations of the solar electricity generation of PV Parks. Thus, the computation of the performance of PV parks under cloudy conditions is essential for the optimal operation of the electricity grid. This paper presents solar irradiance measurements to be used for the simulation of the performance of a grid connected PV park, based on the incident global irradiance at the photovoltaic modules. The 150kWp PV Park is located on an inclined roof of an industrial building in Limassol Cyprus (latitude 34.7oN, longitude 32.94oE). The incident irradiance at the PV modules is computed as the sum of three components: the beam component from direct irradiation of the tilted surface, the diffuse component, and the reflected component. The measurements of the diffuse and global horizontal irradiance were recorded on site using a BF-5 Sunshine Sensor and the tilted irradiance using the Sunny SensorBox. The measurements from the BF-5 Sunshine Sensor were previously validated against the measurements from our meteorological station. For the computation of tilted irradiance, three isotropic and seven anisotropic models were used, using only measurements of global irradiance and calculations of solar position and irradiance incidence angle on the PV panels. The solar electricity generation of the park was correlated to the irradiance measurements from the Sunny SensorBox, taking into consideration the interconnection of the Park and the measurements of the module temperature provided by a monitoring system located on-site. The power output of the PV modules to the inverters for different incident irradiance was estimated from the current-volt characteristic curves of the PV modules based on the assumption that the inverters’ maximum power point tracking mechanism adapts instantly to the fluctuations of solar irradiance, and thus, the PV modules are operating always at maximum power output conditions. The influence of the temperature to the power output of the PV modules was also introduced using the temperature coefficients of the PV modules. Results showed a good agreement between measured and calculated power output.
Keywords: Solar electricity generation; Global tilted irradiance; Photovoltaics; Simulation